Civil Rights: rethinking their natural foundation - West, Robin L. (New York Cambridge University Press, 2019)
All of us are entitled to the protections of law against violence, to a high quality education, to decent employment that respects our dignity, and to necessary assistance with our caregiving. Our civil rights are our rights to the protections of ordinary law - not constitutional law, and not only antidiscrimination law - that will ensure that we can participate in civil society, and hence lead flourishing lives. In this innovative work, Robin L. West looks back to nineteenth-century Civil Rights Acts to argue that the point of civil rights law is not only non-discrimination, but also to assure that all of us receive the protection of legal rights that promote human flourishing. Since the 1960s, Supreme Court decisions on civil rights issues have focused on non-discrimination and thus have 'hollowed out' this broader meaning of civil rights law. This book reconceives civil rights as a set of legal guarantees that all will be included in the legal, political, economic and social projects central to civil society.
Keywords: United States; Civil rights--Philosophy